2003
DOI: 10.1212/01.wnl.0000091868.28557.b8
|View full text |Cite
|
Sign up to set email alerts
|

Left/right asymmetry of atrophy in semantic dementia

Abstract: Patients with left and right predominant SD present with distinct behavioral-cognitive profiles. Characterization of these features may assist in the early and accurate diagnosis of SD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

27
274
3
6

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 339 publications
(312 citation statements)
references
References 62 publications
27
274
3
6
Order By: Relevance
“…More recently, Williams et al [79] have revealed in a group of frontotemporal dementia patients (including both temporal and frontal variants) that semantic breakdown, measured by non-verbal associative knowledge and naming, was mainly correlated with extensive loss of GM volume throughout the left anterior temporal lobe. Our findings also fit with those of Thompson et al [73] who showed different patterns of cognitive disturbances (predominant in the domain of word-finding and person-specific knowledge, respectively) according to the predominantly altered temporal lobe. Other authors have suggested the right temporal lobe to be critical to person-specific knowledge (e.g., [20]).…”
Section: Discussionsupporting
confidence: 92%
“…More recently, Williams et al [79] have revealed in a group of frontotemporal dementia patients (including both temporal and frontal variants) that semantic breakdown, measured by non-verbal associative knowledge and naming, was mainly correlated with extensive loss of GM volume throughout the left anterior temporal lobe. Our findings also fit with those of Thompson et al [73] who showed different patterns of cognitive disturbances (predominant in the domain of word-finding and person-specific knowledge, respectively) according to the predominantly altered temporal lobe. Other authors have suggested the right temporal lobe to be critical to person-specific knowledge (e.g., [20]).…”
Section: Discussionsupporting
confidence: 92%
“…Thus, 13 SD patients were classified as LTLV (mean age 62.0 ± 6.3 years, nine males, four females) and six as RTLV (mean age 62.5 ± 5.7 years, three males, three females) (see Table 1). This is consistent with previous studies showing that LTLV is roughly three times more prevalent than RTLV (Seeley et al, 2005;Thompson et al, 2003). There was no significant difference between LTLV and RTLV for age, education, sex, and interval between MRI scans (Table 1).…”
Section: 32supporting
confidence: 92%
“…Only six patients were found to have greater right temporal atrophy (RTLV), consistent with prior studies suggesting that LTLV is roughly three times more prevalent. 8 The patients with RTLV varied with respect to temporal atrophy severity and asymmetry. Accordingly, from the remaining 19 patients with LTLV, six were chosen to mirror the RTLV group as closely as possible (figure 1).…”
Section: Acquisition Of Mri and Cerebral Volumesmentioning
confidence: 99%